Variability of Presentations and CT-Scan Findings in Children with Neurocysticercosis - Gauchan, E; Malla, T; Basnet, S; Rao, K S (Kathmandu University Medical Journal, 2012)
Background Neurocysticercosis is one of the common neurological morbidities in childhood. Objectives To find the commonest mode of presentation of this disorder in children. The study also aims to find out the age at which it commonly occurs, commonest site affected in the brain and the ethnic group and region most commonly affected in Western Nepal. Methods Retrospective hospital based study carried out in the Department of Pediatrics, Manipal Teaching Hospital, Pokhara from June 2004 to June 2009. Results Over the period of five years, 678 patients were admitted for seizures; out of which 109 patients were diagnosed as having neurocysticercosis (16%). Out of them, 66 (60.5%) were males and 43 (39.4%) were females. The age of presentation varied from 18 months to 16 years, with mean age 9.77 years. The most common age of presentation was between 6-10 years (n=47; 43.1%) and 11-15 years (n=47; 43.1%).Maximum number of patients were from Kaski district (n=41; 37.6%) followed by Syangja (n=34; 31.1%).The commonest presentation was with seizures (n=85; 77.9 %); generalised seizures was present in 45 patients (52%). Psychiatric manifestations were present in 3 patients (2.7%). The lesions were found mostly in the parietal region (n=65; 59.6 %). Most of the lesions were single (n=89; 81.6%). Out of 109 patients, 74 patients (67.8%) improved without any recurrence of symptoms on two years follow-up. Conclusion Neurocysticercosis is a preventable zoonotic disease which results in significant morbidity in children where sanitary measures are inadequate. Any child presenting with a first episode, afebrile seizure should be screened for neurocysticercosis provided other common causes are ruled out. DOI: http://dx.doi.org/10.3126/kumj.v9i2.6281 Kathmandu Univ Med J 2011;9(2):17-21